Application of Environmentally-Based Student Worksheets on the Observational Skills - Nurhanie, Shahiga Baiq; Arsyad, Muhammad; Khaeruddin, Khaeruddin (Jurnal Pendidikan Fisika, 2025)
This study investigates the impact of environmentally-based student worksheets on enhancing observational skills in physics education. Active student participation is crucial for effective learning, and innovative tools such as these worksheets are designed to improve student engagement and skill development. The study specifically aims to: (1) assess the observational skills of grade X students at State Senior High School 2 Mamuju using environmentally-based student worksheets; (2) compare these skills with those of students using conventional student worksheets; and (3) analyze the differences in observational skills between the two groups. A quasi-experimental design was employed, using a posttest-only control group method. The independent variable was the type of student worksheet (environmentally-based vs. conventional), while the dependent variable was students' observational skills. The sample included grade X MIPA students, with 33 students in the experimental group (using environmentally-based worksheets) and 35 students in the control group (using conventional worksheets) selected through purposive sampling. Results demonstrated that students using environmentally-based student worksheets exhibited significantly higher observational skills (mean score: 16.27, high category) compared to those using conventional worksheets (mean score: 12.4, moderate category). Statistical analysis confirmed a significant difference between the groups. These findings suggest that integrating environmentally-based student worksheets is an effective strategy for improving observational skills, fostering better engagement, and enhancing students' understanding of physics concepts, particularly in the context of Newton’s laws of motion. The study emphasizes the importance of context-rich, interactive learning tools for science education.